APPROACHING LANDSCAPES IN FINE ARTS, WITH YOUNG SCHOOLCHILDREN, THROUGH FLIPPED CLASSROOM STRATEGY. APPLICATIONS WITHIN THE CONTEXT OF eTWINNING PROJECTS - GABRIELA ILEANA CRIȘAN; ION ALBULESCU (Romanian Review of Geographical Education, 2018)
In the present study, we conducted analyses of artwork that represents elements from the natural and man-made environment and established their compliance with the real world. We also present a comparative approach of young schoolchildren’s artwork, having the landscape and other environment elements as a main theme. The research took place throughout the 2015-2016 school year, on a representative sample of 20 pupils from Romania, participants in the eTwinning programme. We used the flipped classroom learning strategy in order to introduce the pupils to the Impressionist plastic art form of expression. The teaching experiment included five stages: initial testing, studying a tutorial at home, practicing painting techniques in the classroom, getting feedback from the teachers, and final assessment. We analysed the pupils’ artwork from the point of view of framing in the plastic theme. We have taken into account the sub-criteria: to observe the norms of the artistic movement, the chosen technique, the type of chosen tool/material, and the manner of brush strokes.